Spatial and Seasonal Characterization of the Physico-Chemical Quality of the Water of the Tovè River in the Southern Benin (West Africa) - DJIDOHOKPIN, Gildas; SOSSOUKPE, EDMOND; BOKOSSA, JANVIER KOUESSIVI HERVE; Tamesse, Joseph L.; FIOGBE, EMILE DIDIER (My University, 2017)
A characterization of the water of the Tovè River has been achieved in order to have basic data for subsequent investigations on the ichthyofauna’s state of this river and to develop appropriate measures to avoid the loss of its aquatic biodiversity. Thus, the spatio-temporal variations of dissolved oxygen, pH, temperature, conductivity, salinity, water transparency, depth, velocity, total dissolved solids (TDS), nitrite (NO2-), nitrate (NO3-), phosphate (PO43-), magnesium (Mg2+), calcium (Ca2+), sulfates (SO42-) and ammonium (NH4+) were surveyed from October 2015 to September 2016. The correlation analysis of the collected data showed strong correlations between these water parameters. The Kruskal-Wallis test showed that the variation of the physico-chemical parameters of the River was strongly influenced by hydrological seasons (p < 0.001). Excepted the calcium, magnesium and temperature values, all the surveyed parameters of the Tovè River waters presented relative high values during the rainy and flood seasons which were mostly beyond the MDDEFP guideline values relative to the protective criteria of the aquatic life (chronic effect), due to runoff drainage, which includes all chemicals generated by anthropogenic activities (manure waste, biomedical waste, leaching, domestic wastewater discharges) along the bank.
Keywords: Tovè River; Rainy Season; Dry Season; Physico-Chemical Parameters; Benin.